STUDY ABUNDANCE PLANKTONIC DIATOM (Bacillariophyta) WITH NITRATE AND PHOSPHATE CONCENTRATION IN BELAWAN WATERS PROVINCE NORTH SUMATERA - Mikael H Dolok Saribu; Aras Mulyadi; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Research about abundance of planktonic diatoms with concentration ofnitrate and phosphate in Belawan waters of North Sumatra Province wasconducted in February 2013. The purpose of this study was to know the type ofplanktonic diatom, nitrate and phosphate concentration, diatom communitystructure, determine the relationship between nitrate and phosphate concentrationwith Abundance of diatoms. Samples taken from 4 stations. The sampleidentification was obtained by 16 diatom species. The abundance of diatoms is inthe range of 4,018-4,802 ind/liter. The nitrate concentration of each station is inthe range of 0.261-0.507 mg/l. The concentration of phosphate in the range of0.064-0.126 mg/l. The diversity index is moderate, no dominant type and theuniformity index belongs to the still-balanced waters. The relationship of nitrateand phosphate concentration to diatom abundance is classified as moderate topositive value, the higher the concentration of nitrate and phosphate, the higherthe diatom abundance.Keyword: Belawan Waters, Diatom, Abudance, Nitrate & Phosphate